PERANAN ADVOKAT DALAM MEMBERIKAN BANTUAN HUKUM TERHADAP PELAKU TINDAK PIDANA NARKOTIKA - simanjuntak, Chintya Louisa; Manullang, Herlina (Judge : Jurnal Hukum, 2025)
This study discusses the role of advocates in providing legal assistance to offenders in narcotics cases, highlighting the legal, ethical, and social aspects of law enforcement in Indonesia. Narcotics crimes are considered serious due to their wide-ranging impact on society, thus requiring fair legal representation for every defendant. Based on Law Number 18 of 2003 on Advocates, lawyers are obliged to provide legal assistance without discrimination. This research employs a normative juridical method with statutory, conceptual, and case study approaches, drawing on Law Number 35 of 2009 on Narcotics, the Criminal Procedure Code (KUHAP), and relevant legal literature. The results show that advocates play a vital role from the investigation to the trial stages in ensuring the protection of the suspect’s legal rights and upholding the fair trial In narcotics cases with severe penalties, including imprisonment of five years up to the death penalty, advocates are responsible for preparing proportional defenses, filing legal remedies such as appeals, cassation, or clemency, and safeguarding the right to life as guaranteed by the Constitution. Beyond litigation, advocates also play an educational and social advocacy role in promoting restorative justiceand encouraging a more just, humane, and rehabilitation-oriented legal system for narcotics offenders.